Preference Responses of Wheat Flour Substitution with Jackfruit Seed Flour on Oyster Mushroom Nuggets - Amelia Nirmalawaty; Tiurma Wiliana Susanti Panjaitan; Alamsyah Alamsyah (Postgraduate, University of Mataram, 2023)
The utilization of Jackfruit seeds is still limited as a snack even though it has no less nutritional substances than wheat flour, even the calories and carbohydrate content is lower so it has the potential to be processed into flour and is expected to substitute wheat flour. On the other, public concern about healthy foods with low-fat content has resulted in the need to develop sources of vegetable protein, one of which is oyster mushrooms which are processed into nuggets. This study aims to determine the preference response to oyster mushroom nugget products with jackfruit seed flour substitution The research treatment tested 4 treatment levels of substitution of wheat flour with Jackfruit seed flour, namely P0 (100% Wheat Flour), P1 (80% Wheat Flour + 20% Jackfruit Seed Flour), P2 (60% Wheat Flour + 40% Jackfruit Seed Flour), and P3 (Wheat Flour 40% + Jackfruit Seeds Flour 60%). The results show the substitution of jackfruit seed flour in mushroom nuggets oyster had an effect on the color, aroma, and taste of oyster mushroom nuggets and oyster mushroom nuggets had the best preference in t 20% substitution treatment.